Brain Biopsy for Neurological Diseases of Unknown Etiology in Critically Ill Patients: Feasibility, Safety, and Diagnostic Yield. Issue 6 (10th January 2022) - Mathon, Bertrand; Favreau, Malory; Degos, Vincent; Amelot, Aymeric; Le Joncour, Alexandre; Weiss, Nicolas; Rohaut, Benjamin; Le Guennec, Loïc; Boch, Anne-Laure; Carpentier, Alexandre; Bielle, Franck; Mokhtari, Karima; et al.
Abstract : OBJECTIVES: Brain biopsy is a useful surgical procedure in the management of patients with suspected neoplastic lesions. Its role in neurologic diseases of unknown etiology remains controversial, especially in ICU patients. This study was undertaken to determine the feasibility, safety, and the diagnostic yield of brain biopsy in critically ill patients with neurologic diseases of unknown etiology. We also aimed to compare these endpoints to those of non-ICU patients who underwent a brain biopsy in the same clinical context. DESIGN: Monocenter, retrospective, observational cohort study. SETTING: A French tertiary center. PATIENTS: All adult patients with neurologic diseases of unknown etiology under mechanical ventilation undergoing in-ICU brain biopsy between January 2008 and October 2020 were compared with a cohort of non-ICU patients. INTERVENTIONS: None. MEASUREMENTS AND MAIN RESULTS: Among the 2, 207 brain-biopsied patients during the study period, 234 biopsies were performed for neurologic diseases of unknown etiology, including 29 who were mechanically ventilated and 205 who were not ICU patients. Specific histological diagnosis and final diagnosis rates were 62.1% and 75.9%, respectively, leading to therapeutic management modification in 62.1% of cases. Meningitis on prebiopsy cerebrospinal fluid analysis was the sole predictor of obtaining a final diagnosis (2.3 [1.4–3.8]; p = 0.02). ICU patients who experienced therapeutic management modification after the biopsy had longer survival ( p = 0.03). The grade 1 to 4 (mild to severe) complication rates were: 24.1%, 3.5%, 0%, and 6.9%, respectively. Biopsy-related mortality was significantly higher in ICU patients compared with non-ICU patients (6.9% vs 0%; p = 0.02). Hematological malignancy was associated with biopsy-related mortality (1.5 [1.01–2.6]; p = 0.04). CONCLUSIONS: Brain biopsy in critically ill patients with neurologic disease of unknown etiology is associated with high diagnostic yield, therapeutic modifications and postbiopsy survival advantage. Safety profile seems acceptable in most patients. The benefit/risk ratio of brain biopsy in this population should be carefully weighted.